Bioresorbable polymeric materials – current state of knowledge - Wiśniewska, Kamila; Rybak, Zbigniew; Wątrobiński, Marcin; Struszczyk, Marcin H.; Filipiak, Jarosław; Szymonowicz, Maria (Polimery, 2021)
Bioresorbable materials are used in medicine for fi xing, correcting or stabilizing bones in various anatomical areas, and the market for such materials is growing rapidly worldwide. The use of polymers for their production is associated with the ability to control their properties. They are prepared from bioresorbable materials with variable surface, geometry, porosity, as well as mechanical and surface properties. They support bone healing and are suitable for tissue regeneration due to their biodegradability and biocompatibility. We believe that materials from biodegradable polymers will play an increasingly important role in future medicine.